Implementation of the “Merdeka Belajar” Curriculum in the Industrial 4.0 Era - Rohmah, Azizatul Nur; Sari, Irasikah Julia; Rohmah, Nur Lailatur; Syafira, Riska; Fitriana, Fitriana; Admoko, Setyo (Mitra Edukasi dan Publikasi, 2023)
Revolution 4.0 is marked by the era of digitalization, namely by the rapid development of science and technology. Technology in the industrial era 4.0 caused the human role to be shifted. This causes changes in how to work and relate to one another. In the digital era, the education system is expected to realize that students have skills capable of critical thinking and problem solving, creative and innovative skills, communication and collaboration skills, and skilled use of information and technology. Therefore, the purpose of this article is to determine the effectiveness of the independent learning curriculum in implementing the learning process and the constraints and solutions that can be provided in implementing the independent learning curriculum in the learning process. The research method used is the method of literature study and qualitative research. The results obtained from the research that has been carried out are the application of the “Merdeka” curriculum, the effectiveness of the “Merdeka” curriculum, the advantages of implementing an “Merdeka” curriculum, and the constraints of implementing an “Merdeka” curriculum. Implementing the independent learning curriculum is more straightforward than the 2013 one. The effectiveness of the 2013 curriculum is quite good and beneficial in terms of students who are free to choose according to their interests and talents and teachers who only need to explain some of the material's content. Of course, in implementing this “Merdeka” curriculum, there are obstacles, such as various media.